2016
DOI: 10.1038/ncb3378
|View full text |Cite
|
Sign up to set email alerts
|

Chronic p53-independent p21 expression causes genomic instability by deregulating replication licensing

Abstract: The cyclin-dependent kinase inhibitor p21(WAF1/CIP1) (p21) is a cell-cycle checkpoint effector and inducer of senescence, regulated by p53. Yet, evidence suggests that p21 could also be oncogenic, through a mechanism that has so far remained obscure. We report that a subset of atypical cancerous cells strongly expressing p21 showed proliferation features. This occurred predominantly in p53-mutant human cancers, suggesting p53-independent upregulation of p21 selectively in more aggressive tumour cells. Multifac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

23
282
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 260 publications
(315 citation statements)
references
References 86 publications
23
282
0
10
Order By: Relevance
“…Indeed analyzing the data in our report, we found out that this was the case. 5 TLS is the main DNA damage tolerance pathway of the cell representing an important "defense" line, as it mends the lesions that escape from the surveillance of the error-free DNA repair mechanisms, allowing completion of chromosome replication. 7 Apparently, prolonged p21 WAF1/Cip1 expression could lead to reduced TLS activity contributing together with re-replication to replication fork stalling, collapse and generation of double strand breaks fuelling genomic instability (Fig.…”
Section: Cip1mentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed analyzing the data in our report, we found out that this was the case. 5 TLS is the main DNA damage tolerance pathway of the cell representing an important "defense" line, as it mends the lesions that escape from the surveillance of the error-free DNA repair mechanisms, allowing completion of chromosome replication. 7 Apparently, prolonged p21 WAF1/Cip1 expression could lead to reduced TLS activity contributing together with re-replication to replication fork stalling, collapse and generation of double strand breaks fuelling genomic instability (Fig.…”
Section: Cip1mentioning
confidence: 99%
“…In line with this notion, we showed that protracted p21 WAF1/Cip1 expression abrogated the property of PCNA to regulate the degradation cycle of the replication licensing factors Cdt1 and Cdc6, 6 triggering re-replication. 5 Consecutively, p21…”
mentioning
confidence: 99%
See 3 more Smart Citations